Development of smart farming - a detailed study - M. Chidambaranathan, C; Handa, S.S.; Ramanamurthy, M.V. (International Journal of Engineering and Technology, 2018)
Agriculture is the backbone of every country. The country’s development is not due to Industrial development alone, but also due to the agriculture development. The Country like India depends upon the 70 percent of the agriculture. In the recent year’s agriculture productions got down due to the natural disasters like flood, famine and etc., hence the country should implement the latest technology to overcome the problems in agriculture. Recently Internet of Things (IoT) is the latest technology used in all the fields. By 2020, IoT would be effectively implemented in every field. In agriculture, Smart Farming which is involves connecting sensors and internet to collect various parameters like temperature, humidity, moisture and etc., and share with the farmers periodically. It is the latest technology which improves the agriculture as well as country economy. In this paper we will discuss the various methods of smart farming.